Scale Insects (Hemiptera: Coccoidea) on Myrciaria dubia (Myrtaceae) in Brazil - Wolff, V. R. S.; Kondo, T.; Peronti, A. L. B. G. [UNESP]; Noronha, A. C. S. (Entomological Soc Brasil, 2016)
Commercial cultivation of the fruit tree Myrciaria dubia (Myrtaceae) is being developed in Brazil but phytophagous insects, including scale insects (Hemiptera: Coccoidea), can become pests in plantations. The coccids Ceroplastes jamaicensis White, Coccus viridis (Green), Parasaissetia nigra (Nietner), Pseudokermes vitreus (Cockerell) (Coccidae), and the diaspidid Pseudaonidia trilobitiformis (Green) were collected on M. dubia in the municipality of Belem and Tome-Acu, state of Para (PA), metropolitan and Northeast Para mesoregions, Brazil. A key to species of Coccoidea recorded on M. dubia, based on adult females, is provided. Photographs for all scale insects reported on M. dubia are provided. Ceroplastes jamaicensis is recorded for the first time for Brazil and is herein reported for the first time associated with this host.
Keywords: Amazon basin; camu-camu; Diaspididae; native fruit tree